In vitro susceptibility of a penicillin-resistant and tolerable isolate of Streptococcus pneumoniae to combination therapy - Arnab Majhi; Ajeya Nandi; Rana Adhikary; Sayantika Mahanti; Biswadev Bishayi (Journal of Infection in Developing Countries)
Introduction: Preference for combination therapy to treat infection due to multidrug-resistant S. pneumoniae (MDRSP) has not been well elucidated in previous studies. Methodology: In the present study, 19 antibiotics in combinations were tested against an MDRSP isolate. In vitro susceptibility studies including minimum inhibitory concentration (MIC), minimal bactericidal concentrations (MBC) and disk agar diffusion (DAD), tolerance to resistant antibiotics, checkerboard assay, time-kill curve, hemolytic assay, and autolysis assay were performed on the test strain to study its in vitro susceptibility to combination therapy. Results: From the checkerboard assay and time-kill curve, it was observed that a combination of levofloxacin (MIC, 16 µg/mL) and ceftriaxone (MIC, 2 µg/mL), at sub-MIC concentration was synergistic and most effective against the MDRSP isolate (penicillin MIC, > 64 µg/mL). Hemolytic activities also increased significantly with combination therapy compared to monotherapy (p < 0.05). Moreover, the hemolytic activity of levofloxacin in combination with ceftriaxone was better than ciprofloxacin plus ceftriaxone or cefepime. The autolysis rate was also found to increase rapidly within one hour of exposure to levofloxacin plus ceftriaxone, and this was found to be significantly different from the other combinations at the fifth and sixth hour post incubation (p < 0.05). Conclusions: This data suggests that this combination is bactericidal in vitro, and requires further studies in in vivo models for treatment against MDRSP infections.